Sudden infant death syndrome: How much mothers and health professionals know - (:unkn) unknown (WILEY, 2011)
Background: Behavioral risk factors are associated with sudden infant death syndrome (SIDS). Education about the risk factors of SIDS is important for prevention. Our aim was to determine the knowledge and attitude of parents and health professionals about SIDS. Methods: A total of 174 health professionals and 150 mothers were enrolled in this study. Mothers' data were collected by telephone interview and health-care professionals were interviewed by the same investigator. Results: Only 39% of mothers were aware of SIDS. Forty-six percent of the mothers preferred a supine sleeping position for their infant and 16% of the parents were bed-sharing with their infants. Seventy-three percent of health professionals selected side, 17% supine and 10% prone sleeping position as the safest sleeping position. Frequencies for awareness of risk factors were: bed-sharing (75%), soft bedding (70%), pillow use (52%), toys in bed (90%), high room temperature (67%) and smoking (88%). Total knowledge score of health professionals who selected supine sleeping position as the safest was significantly higher (P < 0.001). Conclusion: Most of the mothers were unaware of SIDS and less than half preferred a supine sleeping position for their infant. Only 72% of health professionals recommended a certain sleeping position during family interviews. Health professionals are more often recommending the side sleeping position or prone. Education of families and health professionals for the risk factors of SIDS may reduce the number of deaths from SIDS in Istanbul.
Keywords: bed-sharing; child; sleep; sleeping position; sudden infant death syndrome; CHILD-CARE PRACTICES; RISK-FACTORS; SLEEP POSITION; PACIFIERS